Analisis Efektivitas Kinerja dengan Pendekatan Balanced Scorecard (Studi Pada Kantor Wilayah XVI Direktorat Jenderal Kekayaan Negara Manado) - Daryono, Thomas Dwi; Rantung, Ventje V (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. This study aimed to measure the effectiveness of using the Balanced Scorecard performance and analyze the balance performance at the Regional Office of Directorate General of State XVI Manado. This study uses a quantitative approach to data analysis frequency range of criteria. Respondents consisted of internal respondents that all employees of the Regional Office of Directorate General of State XVI Manado and external respondents that the partners. The results showed that the performance of the Regional Office of Directorate General of State XVI Manado is good or effective but not balanced. Imbalance occurred in the performance of the external performance is higher than the internal performance, higher financial performance than non-financial performance, the performance of which focuses on factors yield higher performance than triggers and performance that focuses on the more dominant performance than focusing on people. Performance measurement is expected to assist the Regional Office of Directorate General of State XVI Manado in formulating a strategy to improve performance in the future.